Zircon and muscovite ages, geochemistry, and Nd–Hf isotopes for the Aktyuz metamorphic terrane: Evidence for an Early Ordovician collisional belt in the northern Tianshan of Kyrgyzstan - Kröner A.; Alexeiev D.V.; Hegner E.; Rojas-Agramonte Y.; Corsini M.; Chao Y.; Wong J.; Windley B.F.; Liu D.; Tretyakov A.A. (My University, 2012)
The Aktyuz metamorphic terrane in the Kyrgyz northern Tianshan consists of granitoid gneisses and migmatites with subordinate paragneisses, greenschists, presumed meta-ophiolites, and garnet amphibolite dykes that contain HP eclogite relicts. The gneisses and migmatites were previously considered to be Archaean and Palaeoproterozoic in age on the basis of α-Pb and U–Pbmultigrain zircon dating. Zircons from a post-tectonic granite were previously dated at 692±15 Ma, constraining the time of main deformation and metamorphism in the Aktyuz terrane to the Precambrian. The chemical characteristics ofmost granitoid samples are consistent withmelting of chemically evolved crustal material, which is supported by Nd and Hf isotopic data. Zircon U–Pb SHRIMP ages were obtained for the main varieties of metamorphic rocks, for a gabbro of a low-grade ophiolite complex and for several post-kinematic igneous rocks. In addition,metamorphicmuscovitewas dated by the 40Ar–39Ar method, andwhole-rock Sm–Nd isotopic systematics were obtained on several granitoid rocks. Our magmatic zircon crystallization ages for granitoid gneisses in the Aktyuz and Kemin Complexes range from778±6 to 844±9 Mawhich we interpret to reﬂect the time of magmatic emplacement of the gneiss protoliths. These rocks reﬂect an episode of Neoproterozoic granitoid magmatism, which is also documented in southern Kazakhstan, the Kyrgyz Middle Tianshan, the Chinese Central Tianshan and the TarimCraton. Nd and Hf isotopic systematics showthese rocks to be derived from Mesoproterozoic to Archaean sources. The calc-alkaline composition of these rocks seems compatiblewith a subduction setting, but ismost likely inherited fromthe source, therefore the tectonic scenario for emplacement of the gneiss protolith remains unknown. Two ages of 562±7 and 541±3 Ma and negative εNd(t)-values for granitoid gneisses document a later crustal melting episode. Muscovite 40Ar/39Ar ages of ca. 470 Ma for Aktyuz gneisses constrain the main fabric-forming metamorphism to the Early Palaeozoic. A migmatitic paragneiss, which was previously interpreted as Palaeoproterozoic, contains detrital zircons with an age spectrum from 503 to 1263 Ma; the youngest grain suggests a maximum Cambrian age of protolith deposition. An ophioliticmetagabbro of the Kemin Complex yielded an Early Cambrian age of 531±4 Ma,which is close to the age of ophiolites in the adjacent Djalair–Naiman belt of Kazakhstan, suggesting a possible genetic link. Two samples of quartz diorite fromthe post-kinematic Dolpran pluton yielded Early Ordovician zircon ages of 471.9±3.5 and 472.0±3.1 Ma. The presence of a 783±7 Ma xenocrystic zircon points at Precambrian crust at depth,whichmay explain an earlier, discordant apparent age obtained bymultigrain zircon dating of this pluton. Undeformed rhyolite and basalt in the East Kyrgyz Range, previously classiﬁed as Neoproterozoic and Cambrian, yielded Late Ordovician ages of 451.9±4.6 and 448.9±5.6 Ma respectively.
Keywords: Collision; Crustal-melt granitoids; Kyrgyzstan; Nd and Hf isotopes; Northern Tianshan; Zircon geochronology; Muscovite Ar-dating; Tectonic model; Zircon age; Палеозой::Ордовикская; Paleozoic::Ordovician